2017
DOI: 10.1093/jipm/pmx009
|View full text |Cite
|
Sign up to set email alerts
|

Pest Management Strategies for Bed Bugs (Hemiptera: Cimicidae) in Multiunit Housing: A Literature Review on Field Studies

Abstract: Bed bugs (Cimex lectularius L.) continue to increase as serious pests in the built environment. These insects are particularly problematic in low-income multiunit housing buildings, where infestations are difficult to control, tend to become chronic, and the locations serve as reservoirs from which bed bugs disperse. This document reviews and reports on published accounts and validations of various methods to detect and manage bed bugs in these urban settings. The analysis demonstrates that programs using IPM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…Bed bug infestations cause health problem predominantly in low-income housing communities since ineffective pest management practices are frequently associated with low-income households (14). Especially the multiunit housing buildings are affected where infestations chronically persist serving as dispersal foci of the pest (15). Studying the resurgence of the pest in Canada, Hwang et al found that bed bugs started appearing in homeless shelters (16).…”
Section: Introductionmentioning
confidence: 99%
“…Bed bug infestations cause health problem predominantly in low-income housing communities since ineffective pest management practices are frequently associated with low-income households (14). Especially the multiunit housing buildings are affected where infestations chronically persist serving as dispersal foci of the pest (15). Studying the resurgence of the pest in Canada, Hwang et al found that bed bugs started appearing in homeless shelters (16).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, integrated pest management strategy which uses various non-chemical techniques/ tools before chemicals becomes more prevalence and promising in last decades. Furthermore, IPM considered as practical strategy in urban environment where bed bug control is challenging in low-income communities and multiunit housing building (18). Due to the high cost of bed bug elimination (about $ 0.78 per m 2 ) by pest control services, residents in low-income communities prefer to control the infestation themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Little studies have been documented the usefulness of IPM strategy for control bed bugs (5,13,18,19). But there are no studies on resident education and self-implementation of IPM strategy for control of bed bug infestation.…”
Section: Introductionmentioning
confidence: 99%
“…The people should be educated about bed bug controls via Integrated Pest Management (IPM) approach. This is the collection of physical methods like killing and eliming the insects using heating, freezing, steaming, vacuuming, washing and drying and chemical tactics based on recommended insecticide dosage (32).…”
Section: Discussionmentioning
confidence: 99%